The 2nd Canadian Conference on Computer and Robot Vision (CRV'05)
DOI: 10.1109/crv.2005.47
|View full text |Cite
|
Sign up to set email alerts
|

Histogram Equalization using Neighborhood Metrics

Abstract: We present a refinement of histogram

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…The ideal greyscale image histogram is perfectly flat and makes use of every available grey value in the image format [6,12]. Application of GHE on illumination affected images, it is found that histograms do not use the entire range of gray scale value and the histograms are not flat [13].…”
Section: Neighborhood Metrics (Nm)mentioning
confidence: 99%
See 4 more Smart Citations
“…The ideal greyscale image histogram is perfectly flat and makes use of every available grey value in the image format [6,12]. Application of GHE on illumination affected images, it is found that histograms do not use the entire range of gray scale value and the histograms are not flat [13].…”
Section: Neighborhood Metrics (Nm)mentioning
confidence: 99%
“…Face recognition accuracy improves as results of enhancing the facial regions affected by blur and shadow. Neighbourhood metrics in use are Voting metric [6,12,13,14], Distinction metric [6,12,13,14], fuzzy approach on the neighbourhood pixels [14].…”
Section: Neighborhood Metrics (Nm)mentioning
confidence: 99%
See 3 more Smart Citations